Partial element equivalent circuit modeling of distributed and lumped time-varying dielectric phenomena - Romano, Daniele; Pettanice, Giuseppe; Štumpf, Martin; Lager, Ioan E.; Ekman, Jonas; Franek, Ondřej; Valentini, Roberto; Di Marco, Piergiuseppe; Santucci, Fortunato; Antonini, Giulio (My University, 2025)
Time-varying (TV) materials have recently gained considerable attention for their ability to manipulate electromagnetic (EM) waves and improve the performance beyond the limits of conventional time-invariant materials. In addition, distributed TV capacitors are becoming more attractive to achieve particular effects. This work presents a systematic approach to modeling TV dielectrics by incorporating TV capacitors in the framework of the partial element equivalent circuit (PEEC) method. Thus, the standard formulation of the PEEC method is modified to include TV dielectrics and lumped elements for general 3D geometries directly in the time domain (TD). It is shown that this is possible through TV capacitances and voltage-controlled current sources. Four numerical examples validate the proposed approach.

Time-varying (TV) materials have recently gained considerable attention for their ability to manipulate electromagnetic (EM) waves and improve the performance beyond the limits of conventional time-invariant materials. In addition, distributed TV capacitors are becoming more attractive to achieve particular effects. This work presents a systematic approach to modeling TV dielectrics by incorporating TV capacitors in the framework of the partial element equivalent circuit (PEEC) method. Thus, the standard formulation of the PEEC method is modified to include TV dielectrics and lumped elements for general 3D geometries directly in the time domain (TD). It is shown that this is possible through TV capacitances and voltage-controlled current sources. Four numerical examples validate the proposed approach.
Partial element equivalent circuit modeling of distributed and lumped time-varying dielectric phenomena
Keywords: partial element equivalent circuit method; time-varying media; computational electromagnetics; partial element equivalent circuit method; time-varying media; computational electromagnetics